Exosomes From Induced Pluripotent Stem Cell–Derived Cardiomyocytes Promote Autophagy for Myocardial Repair. Issue 6 (17th March 2020) - Santoso, Michelle R.; Ikeda, Gentaro; Tada, Yuko; Jung, Ji‐Hye; Vaskova, Evgeniya; Sierra, Raymond G.; Gati, Cornelius; Goldstone, Andrew B.; von Bornstaedt, Daniel; Shukla, Praveen; Wu, Joseph C.; Wakatsuki, Soichi; et al.
Abstract : Background: Induced pluripotent stem cells and their differentiated cardiomyocytes (iCMs) have tremendous potential as patient‐specific therapy for ischemic cardiomyopathy following myocardial infarctions, but difficulties in viable transplantation limit clinical translation. Exosomes secreted from iCMs (iCM‐Ex) can be robustly collected in vitro and injected in lieu of live iCMs as a cell‐free therapy for myocardial infarction. Methods and Results: iCM‐Ex were precipitated from iCM supernatant and characterized by protein marker expression, nanoparticle tracking analysis, and functionalized nanogold transmission electron microscopy. iCM‐Ex were then used in in vitro and in vivo models of ischemic injuries. Cardiac function in vivo was evaluated by left ventricular ejection fraction and myocardial viability measurements by magnetic resonance imaging. Cardioprotective mechanisms were studied by JC‐1 (tetraethylbenzimidazolylcarbocyanine iodide) assay, immunohistochemistry, quantitative real‐time polymerase chain reaction, transmission electron microscopy, and immunoblotting. iCM‐Ex measured ≈140 nm and expressed CD63 and CD9. iCM and iCM‐Ex microRNA profiles had significant overlap, indicating that exosomal content was reflective of the parent cell. Mice treated with iCM‐Ex demonstrated significant cardiac improvement post–myocardial infarction, with significantly reduced apoptosis and fibrosis. In vitro iCM apoptosis was significantly reduced by hypoxia and exosome biogenesis inhibition and restored by treatment with iCM‐Ex or rapamycin. Autophagosome production and autophagy flux was upregulated in iCM‐Ex groups in vivo and in vitro. Conclusions: iCM‐Ex improve post–myocardial infarction cardiac function by regulating autophagy in hypoxic cardiomyoytes, enabling a cell‐free, patient‐specific therapy for ischemic cardiomyopathy.